New Literacies for the Knowledge Society - Mioduser, David; Nachmias, Rafi; Forkosh-Baruch, Alona (International Handbook of Information Technology in Primary and Secondary Education, 2008)
The notion of literacy evolved over time from being strictly focused on the realm of reading/writing skills, to embracing the comprehensive set of skills needed by individuals to learn, work, socially interact and cope with the needs of everyday life. Literacies are cultural constructs, closely tied to the technologies both affording and demanding their evolvement. In the "knowledge society", the widespread impact of advanced Information and Communication technologies (ICT) on the lives of individuals and societies, arouses the need to revise current perspectives on literacy and to identify and define new relevant literacies. In this chapter, seven such literacies will be defined and discussed, concerning multimodal information processing, navigating the infospace, interpersonal communication, visual-literacy, hyper-literacy (hyperacy), personal information management (PIM), and coping with complexity.
Keywords: TICE; numérique